PENGARUH MINAT BELAJAR DAN BIAYA PENDIDIKAN TERHADAP PRESTASI BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Wati, Ayu Sulistio; Nas, Syakdanur; Gimin, Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims is to see the effect of learning interest and education cost on student learning achievement of economic education study program student FKIP Universitas Riau with quantitative descriptive research methods using multiple regression analysis. The sampling techniques uses random sampling Population of this research was 115 respondent and taking 54 respondent for the sample. Based on the results of research and data analysis using multiple linear regression analysis of learning interest (X1), education costs (X2) and learning achievement (Y) obtained the equation Y = 2407+ 0.0151+ 2.840E-82 Where the results of the study show that X1 and X2 are simultaneous effect on Y. Based on the results of the research, it was found that the coefficient of determination (R2) was 42.3%, which means 42.3% of learning achievement was influenced by interest in learning and education costs while the remaining 57.7% was influenced by other independent variables not included in this research. The result of this reseach show that learning interest and education cost has a positive effect on student learning achievement. Thus, the highest learning interest and having a adequate educational cost will make a good learning process for student.Key Words: Learning Interest, Education Cost, Learning Achievement